1989
DOI: 10.1037/0022-0663.81.1.115
|View full text |Cite
|
Sign up to set email alerts
|

Headings as memory facilitators: The importance of prior knowledge.

Abstract: Ninety-four college student subjects read a 4,840-word passage on organization in memory with headings either present or absent. Those subjects who were enrolled in a college course on human memory were defined as the high-preexisting-knowledge subjects, and those subjects who had never been enrolled in such a course were defined as the low-preexisting-knowledge subjects. An analysis of the scores on the multiple-choice retention test revealed that the only significant facilitative effect of the headings was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

1990
1990
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…Several researchers examined the effectiveness of headings for low/high domain knowledge participants, but no consensus was reached. Wilhite (1989) found that compared with no-headings, headings improved the performance of participants with high domain knowledge more than those with low domain knowledge. In contrast, Goldman and Duran (1988) provided evidence that headings were more effective for low domain knowledge participants.…”
Section: Domain Knowledge and Readingmentioning
confidence: 88%
“…Several researchers examined the effectiveness of headings for low/high domain knowledge participants, but no consensus was reached. Wilhite (1989) found that compared with no-headings, headings improved the performance of participants with high domain knowledge more than those with low domain knowledge. In contrast, Goldman and Duran (1988) provided evidence that headings were more effective for low domain knowledge participants.…”
Section: Domain Knowledge and Readingmentioning
confidence: 88%
“…In essence, the subjects' memory for content-specific information may be primed by the pre-test, thus confounding the patterns observed on the experimental inventories. Wilhite (1989), summarizing some of his previous work (Wilhite, 1988), observed the possible confounding influences of a familiarity pre-test in his studies of the effects of headings in text and noted that "for the subjects with high levels of pre-existing knowledge, the pretest questions contributed to the facilitative effect of the headings" (p. 115).…”
Section: Direct Pre-testmentioning
confidence: 95%
“…Another obvious way to control the effects of familiarity is to directly manipulate subjects' familiarity through pre-training on the concepts and content of the experimental materials (Linde & Bergstrom, 1988;Barnes et al, 1989;Stahl et al, 1989;Wilhite, 1989).…”
Section: Pre-trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Οι τίτλοι κατονομάζουν άμεσα τα θέματα των κειμένων και μεταβιβάζουν σιωπηρά την οργάνωση εκείνων των θεμάτων από τη θέση που κατέχουν στο κείμενο. Κατά συνέπεια, η παρουσία των τίτλων μπορεί να βοηθήσει τη μνήμη για το περιεχόμενο και τη δομή ενός κειμένου (Hartley et al, 1980;Hartley & Trueman, 1985;Spyridakis & Standal, 1987;Wilhite, 1989).…”
Section: φκατσούλης 113unclassified